Atomic scale investigation of FCC → HCP reverse phase transformation in face-centered cubic zirconium. (20th February 2023) - Guo, Wenbin; Han, Fuzhou; Li, Geping; Zhang, Yingdong; Ali, Muhammad; Ren, Jie; Wang, Qichen; Yuan, Fusen
Highlights: FCC → HCP reverse phase transformation in an FCC-Zr grain along with a concomitant rotation of 70.5° with α-Zr matrix is observed. The possible interaction among three FCC-Zr grains and a nearby secondary phase particle is discussed. The nature and driving force behind the FCC → HCP reverse phase transformation are revealed. Abstract: Mechanism of FCC → HCP reverse phase transformation in face-centered cubic zirconium (FCC-Zr) along with a concomitant 70.5° rotation of α-Zr matrix were investigated in zircaloy-4 (Zr-4) cladding tube by using transmission electron microscopy (TEM). Results showed that the interaction among a secondary phase particle (SPP) and three FCC-Zr grains resulted in the formation of cross stacking faults in SPP and exerted a drag force on minor axis of the adjacent FCC-Zr phase. Moreover, when the shear stress along [ 1 ¯ 1 ¯ 2 ¯ ] FCC-Zr direction was large enough to initiate the emission of 1 6 [ 1 ¯ 1 ¯ 2 ¯ ] Shockley partial dislocation on every other ( 11 1 ¯ )FCC-Zr close-packed plane, the stacking sequence would change from ABC ABCA to AB ABABA viz. (0001) planes of the daughter HCP phase. Thus, FCC → HCP reverse phase transformation in FCC-Zr was presented.